Biopharmaceutical Classification Based on Solubility and Dissolution: A Reappraisal of Criteria for Hypothesis Models in the Light of the Experimental Observations - Charkoftaki, Georgia; Dokoumetzidis, Aristides; Valsami, Georgia; Macheras, Panos (BASIC & CLINICAL PHARMACOLOGY & TOXICOLOGY, 2010)
The diffusion layer model of drug dissolution is used for the simulation of oral drug absorption as well as for the analysis of experimental data. The governing role of saturation solubility in the rate of dissolution makes this parameter predominant for biopharmaceutical classification purposes. The hypothesis models and criteria associated with the use of solubility and dissolution for the biopharmaceutical classification of compounds and marketed drugs are reviewed in this article. The complex hydrodynamics in the in vitro dissolution apparatuses as well as the motility in the gastrointestinal tract do not allow the application of the diffusion layer model in these systems, as this has been built and verified in the rotating disk device. The solubilizing capacity of gastrointestinal fluids media is higher than the aqueous saturation solubility usually reported and used for biopharmaceutical purposes. Emphasis is given on the reaction-limited model of dissolution which provides a useful alternative not based on diffusion principles. Model independent dissolution parameters are more useful for regulators as our knowledge for the dissolution mechanism(s) under in vivo conditions is limited.